2008
DOI: 10.2355/isijinternational.48.467
|View full text |Cite
|
Sign up to set email alerts
|

Effect of O2 in Heating Atmosphere on Hydraulic Descaling in Hot Rolling of Low Carbon Steel

Abstract: Low carbon steel was oxidized over the temperature range 1 050-1 250°C in O 2 -CO 2 -H 2 O-N 2 gas mixtures. The oxidation times were 15-120 min, and the scales were 130-2 000 mm thick. The experimental parameters were chosen to approximate scale formation under conditions similar to those of reheating furnaces in hot strip mills. In the hydraulic descaling tests, two modes of scale removal were observed. In the first mode, observed in classical three-layer scales that developed an inner porous layer with low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…[12][13][14] These studies showed that mill scale is a layered and brittle material, composed of iron oxides with wustite as a predominant phase. However, depending on parent steel composition some minor oxides are also detected in the mill scales.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] These studies showed that mill scale is a layered and brittle material, composed of iron oxides with wustite as a predominant phase. However, depending on parent steel composition some minor oxides are also detected in the mill scales.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 4 merely comment that the beams can reduce the radiation by y83% around skids. Mogan 7 assumed that skids obstruct 80% of radiation to (34) the slab surface right above the skids. Therefore, the coefficients for this model were calculated using the concept proposed by Lindholm and Leden: 5 (i) coefficients at the distance x from the left hand edge of the computational domain were determined separately for the case of the slab resting on the stationary beam, equation (38), and the walking beam, equation (39) (ii) if the slab spends the portion of time W on the stationary beam, the overall shadowing coefficient at x is calculated using equation (40).…”
Section: Heat Transfer To and Through Beamsmentioning
confidence: 99%
“…A thin scale layer or some parts of the thick scale remain on the substrate surface [3]. The scale residues may grow further if O is available and will undergo structural changes even during cooling after coiling, which is the end of the process [1,7,8]. These scale residues significantly degrade the quality of the final products in several ways [1].…”
Section: Introductionmentioning
confidence: 98%
“…For this reason, it has been known that the weldability is strongly related to the amount of scale residues on the strip surfaces [12]. Research effort has been made to investigate the factors for the adhesion strength between the scales and the steels [7,14]. However, in reality, there are few parameters to vary in the hot rolling process [8].…”
Section: Introductionmentioning
confidence: 99%